General Assessment For Predisposing Factors Of Incisional Hernia, Simple Or Mesh Repair - Al-Obaidi, Munthir (Journal of the Faculty of Medicine Baghdad, 2007)
Background:Incisional hernia is frequently occurring post operative complication after general surgery with occurance rate 2%—–11%, it is either appear soon after operation or late occurring incisional hernia.. Patient &methods: This is a prospective study that was conducted on 84 patients who were admitted at Baghdad Teaching Hospital during the period from Oct. 1999 to Aug. 2001 for repair of incisional hernias. Their ages were ranging from 24-74 years with mean age of (48 ±12). Sixty-nine patients were elective and 15 patients were urgent. Assessment of the patients for the predisposing factors influencing the development of incisional hernia was done and in our study these factors were: - Results:.Wound infection in 66%, midline incision in 58.3%, obesity 55%, chronic obstructive pulmonary disease (COPD), with, respiratory tract infection (RTI) in 44%, multiparty with gynecological and obstetric procedures were 42.9%, diabetes mellitus (D.M) 28.9%, Old age in 21.4%, contaminated bowel surgery 21.4% & finally wound dehiscence with re-suturing in 7.1%. Simple repair was performed in 57 patients and prolene mesh repair was used for 27 patients and follow-up was continued for 6 months except for 8 patients who were lost from follow-up. Results of simple repair was associated with many complications including recurrence in 4 patients, wound infection in 10 patients, seroma in 3 patients deep venous thrombosis (DVT) in one patient. Whereas Mesh repair was followed with minimal complications of seroma in 3 patients and deep venous thrombosis (DVT) in one patient and no recurrence was recorded. Conclusion: wound infection, obesity,emergency surgery ,type of suture material & type of wound all areimportant factors leading to I.H.